Super-Fast Refresh Holographic Display Based on Liquid Crystal Films Doped With Silver Nanoparticles - Hongyue Gao; Zehang Dai; Jicheng Liu; Suna Li; Wen Zhou; Fan Xu; Huilin Fang; Xiaoxi Cheng; Yingjie Yu; Huadong Zheng (IEEE Photonics Journal, 2019)
Holography as a true three-dimensional (3-D) technique is thought to be the ultimate display technique. However, dynamic holographic materials still have problems such as slow refresh, high applied electrical field, etc., to be solved to realize video-rate 3-D display. We present silver nanoparticles (Ag NPs) doped liquid crystal films with very big birefringence and super-fast hologram refresh speed as real-time dynamic holographic medium, which can be applied in holographic video display. And the fastest response time of both build-up and self-erasure of hologram can be up to 0.1 ms, which means the material has the ability to realize a smooth holographic video-rate display. The holographic diffraction efficiency dependent on the intensity of recording light, applied electrical field, etc. is investigated. The maximum diffraction efficiency is measured up to 50% under a low applied electrical field of 0.12 V/ $μ$ m. Real-time holographic videos at red, green, and blue colors are obtained and the process of hologram formation is analyzed, which shows that the LC films doped Ag NPs can be a good candidate for applications of large-size, real-time, color holographic true 3-D display in future.